Analisis Filsafat Keperawatan Tentang Pencegahan Infeksi Luka Operasi Melalui Pemberian Betadine pada Pasien Luka Operasi Apendiktomi - Manuela Monalisa Lindalva Pui; Priyanto Priyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
Surgical wound infection is one of the complications that often occur in postoperative patients and has an impact on increasing morbidity, treatment costs, and length of hospitalization. The purpose of this paper is to analyze surgical wound infection prevention measures through the administration of Betadine in postoperative appendictomy patients reviewed from the perspective of nursing philosophy. The method used is a qualitative approach with an analysis of nursing philosophy that includes three main dimensions, namely ontology, epistemology, and axiology, based on a review of the literature and nursing practice in postoperative wound care. In its implementation, the analysis also considers the standard operational procedures for wound care, aseptic-antiseptic principles, and the patient's clinical context. The results of the analysis show that the administration of Betadine has ontological value as a form of the existence and role of nurses in maintaining the patient's life, epistemological value through the application of scientific knowledge and clinical experience in infection prevention, and axiological value reflected in the ethical attitude, responsibility, and concern of nurses for patient safety. In addition, this action reflects the integration between science, clinical skills, and the values of nursing professionals. Thus, the administration of Betadine is not only understood as a technical measure, but also as a philosophically meaningful nursing practice oriented towards the quality of service and patient safety.